GLOBALIZATION AND YOUTH SPIRITUALITY (British Journal of Global Ecology and Sustainable Development, 2022)
In this article, the theoretical and practical aspects of a new approach to strengthening the effectiveness and quality of educational processes in educational institutions, neighborhoods and families, enriching the national segment in the global network and strengthening the ideological immunity of our youth were discussed in this article. In particular, information is given on the role of the promotion of the national idea in increasing the social activity of young people, the role and participation of political parties in this regard and the specific aspects of improving the legal culture of young people.